Patterns Of Religious Communication To Strengthen Brotherhood In Samura Village, Kecamatan Kabanjahe, Kabupaten Karo - Silvi Suci Apulina; Anang Anas Azhar; Zuhriah (Pena Cendekia Insani, 2022)
The focus of the problem in this study is how the pattern of community communication in strengthening brotherhood in Samura Village, Kabanjahe District, Karo Regency. This study aims to determine how the communication patterns and communication strategies in strengthening the brotherhood among religious believers in Samura Village, Kabanjahe District, Karo Regency. The theories used in this research are communication, interpersonal communication, intercultural communication, communication patterns, and symbolic interaction theory. The research method used in this study is a qualitative descriptive research method. The subjects of this study were eight main informants and one additional informant consisting of two religious leaders, one village government, four general public and one additional informant. The technique of determining informants in this study used the snowball technique. The data analysis technique used is data presentation and conclusion drawing. This study shows that the relationship between religious believers in Samura Village, Kabanjahe District, Karo Regency has a harmonious relationship, whether it is Muslim or Christian. Communication patterns used are interactional patterns or reciprocal relationships in communicating. The strategy used to strengthen the brotherhood is that the community attends the events held, immediately resolves problems, participates in social activities in the village, often conducts interpersonal communication, speaks in a relaxed language, and instills tolerance in oneself.